VARIASI GERAKAN RADIKAL ISLAM DI INDONESIA - Rubaidi, Rubaidi (Analisis: Jurnal Studi Keislaman, 2011)
Islamic  radical  movements  in Indonesia  are various.  Their slogans  about Islamic  union  are  refutable  by  heteroginities  of   groups  and  pattern  of movements. This article portrays about their variety of  movements. Broadly speaking , these groups are divided into two models. First, Islamic radical movements from their origins, such as HTI, Tarbiyah-Ikhwanul Muslimin and  Orthodox-Wahabi   Movement.  Second,  Islamic  radical  movements which have been metamor phosis, though ideologically they are in line with transnational Islamic radical movements in the Middle East. Examples of the second model are among others Front Pembela Islam (FPI), Laskar Jihad (LJ), Majelis Mujahidin Indonesia (MMI). These groups make Indonesian Islam more discursive in terms of  their contestation in gaining supports from Muslims in Indonesia.